Consensus Docking and ADMET Profiling of Pomegranate Leaf Phytochemicals as Potential Dual Inhibitors of Candida albicans Virulence and Ergosterol Biosynthesis - Adam, Shukurana Sulaiman (Journal of Medical Science, 2026)
Background. The increasing resistance of Candida albicans to conventional azole therapies necessitates the discovery of novel antifungal agents that target both metabolic pathways and virulence factors. This in silico study investigated the potential of pomegranate leaf phytochemicals as dual inhibitors of lanosterol 14a-demethylase (CYP51), essential for ergosterol biosynthesis, and secreted aspartic protease 2 (SAP2), a mediator of fungal virulence.Material and methods. A consensus docking approach was employed using three independent engines: AutoDock Vina, AutoDock4, and LeDock. Seven phytochemicals were screened against crystal structures of CYP51 and SAP2. Reliability was validated by redocking, and binding interactions were analysed using 3D and 2D visualisations in Discovery Studio Visualizer (2025). The pharmacokinetics, drug-likeness, and toxicity of the compounds were assessed using the SwissADME and pkCSM tools.Results. Consensus Z-scores identified two distinct classes of inhibitors. Quercetin was predicted as the primary consensus lead against CYP51 (Z-score: -0.98), outperforming fluconazole (Z-score: 0.77) by targeting residues in the substrate-access channel (Ser378, Leu87) rather than traditional heme coordination. Ellagic acid was the primary consensus lead for SAP2, predicted to act as a molecular wedge that may restrict mobility of the enzyme’s flexible flap region (Tyr84). Luteolin and apigenin, identified as secondary lead candidates, exhibited consistent binding across both targets. All prioritised compounds demonstrated favourable ADMET profiles, adhering to Lipinski’s Rule of Five with high gastrointestinal absorption.Conclusions. The findings suggest a specialist-generalist dichotomy among pomegranate phytochemicals. While quercetin and ellagic acid suggest high-potency targeted inhibition, the dual-target engagement of luteolin and apigenin may offer a predicted strategic advantage in reducing the evolutionary probability of resistance. These results provide a molecular framework for the development of plant-derived multi-target antifungal therapies.
Keywords: antifungal agents; Candida albicans; ellagic acid; molecular docking; quercetin